Малозначність діяння в кримінальному праві України - Маломуж, Сергій Ігорович; Маломуж, Сергей Игоревич; Maloniuzh, Sergei I. (My University, 2017)
Дисертація на здобуття наукового сту пеня кандидата юридичних наук за спеціальністю 12.00.08 - кримінальне право та кримінологія; кримінально- виконавче право. - Національний університет «Одеська юридична академія», Одеса, 2017. Дисертація є одним із перших у вітчизняній науці кримінального права спеціальним комплексним дослідженням малозначності діяння з ураху ванням законодавчого досвіду7 окремих зарубіжних країн. Досліджено генезис малозначності діяння в історії кримінального законодавства України, поняття та види малозначності діяння в теорії кримінального права. Визначено малозначність діяння за об’єктом посягання, а також за ознаками об'єктивної та суб’єктивної сторони. Відмежовано малозначність діяння від суміжних понять («відсутність складу злочину», «відсутність події злочину», «звільнення від кримінальної відповідальності», «обставини, що виключають злочинність діяння»), а також досліджено проблеми малозначності діяння в кримінальному судочинстві. Запропоновано удосконалити законодавче визначення поняття малозначності діяння та викласти частину другу ст. 11 КК України в наступній редакції: «Не є кримінальним правопорушенням дія або бездіяльність, які хоча формально і містять ознаки діяння, передбаченого цим Кодексом, але через малозначність не становлять необхідної для кримінального правопорушення суспільної небезпеки, тобто які не могли заподіяти істотної шкоди».

Диссертация на соискание научной степени кандидата юридических наук по специальности 12.00.08 - уголовное право и криминология; уголовно- исполнительное право. - Национальный университет «Одесская юридическая академия», Одесса, 2017. Диссертация является одним из первых специальных комплексных исследований малозначительности деяния в уголовном праве Украины, в котором изучен опыт других государств по определению признаков малозначительности деяния, а также предложены пути усовершенствования части 2 ст. 11 УК Украины. Исследованы генезис малозначительности деяния в истории уголовного законодательства Украины, понятие и виды малозначительности деяния в теории уголовного права. Определена малозначительность деяния по объекту посягательства, а также по признакам объективной и субъективной стороны. Разграничены малозначительность деяния от смежных понятий («отсутствие состава преступления», «отсутствие события преступления», «освобождение от уголовной ответственности», «обстоятельства, исключающие преступность деяния»), а также исследованы проблемы малозначительности деяния в уголовном судопроизводстве, перспективы совершенствования понятия малозначительного деяния. Предложено законодательное определение малозначительности деяния: «Не является уголовным правонарушением действие или бездействие, которое хотя формально и содержат признаки деяния, преду смотренного настоящим Кодексом, но в силу малозначительности, не представляет необходимой для уголовного правонару шения общественной опасности, то есть не могло причинить су щественного вреда».

Thesis for obtaining scientific degree of Candidate of Juridical Science, specialty 12.00.08 - criminal law and criminology: penal law. - The National University «Odessa Law Academy». Odessa. 2017. Dissertation is one of the special complex researches on insignificance of act in criminal law of Ukraine, where the experience of other countries in determining of the value and features of insignificance of act are analyzed for the first time, and it has been suggested the ways of improving its legislative term. It has been investigated the genesis of insignificance of act in the history of criminal law of Ukraine, concepts and types of insignificance of act in the theory of criminal law. the insignificance of act in the criminal law of other countries. In the criminal law of continental legal family the insignificance of act was enshrined as: 1) the reasons for the creation of preferred essential elements of offences (CC of Sweden); 2) the circumstances that exclude criminality of act (CC of Denmark); 3) the grounds for remission from punishment (the Criminal Code of Denmark); 4) the act that is not identified as a crime (CC of Switzerland); 5) grounds for bringing to administrative amenability (CC of Bulgaria). In the criminal legislation of the countries of the “former Soviet Union” the insignificance of act was confirmed as: 1) an act that is not considered as a crime (the most of countries); 2) the grounds for remission from criminal amenability (CC of Lithuania). The insignificance of act was identified as for the object of trespass, and for the features as the objective and subjective sides. It lias been proved that the degree of protection of the object of crime and the possibility of identifying the invasion for this object of the crime by the insignificant of act is in direct ratio correlated with the proximity of the object of criminal influence to the subjects of public relations as a stmctural element of the object of crime. In the legislation determination the insignificance of act the feature “... it was not caused significant damage to physical or legal persons, society or the state” describes the lack of socially dangerous result, and the feature “...it could cause significant damage to physical or legal persons, society or the state” describes the lack of public danger of acting. It is established that the act has been committed in a maimer that is a qualifying feature can not be considered the insignificant one. The insignificant of act can only be the acts which are committed with the intention causing by accidental damage. It has been investigated the division of insignificance of act from similar concepts (“the absence of essential elements of offence”, “the absence of the act of offence”. “ remission from criminal amenability”, “the circumstances that excluding criminality”), the problems of the insignificance of act in criminal judiciary. For solving problems in distinguishing between the concepts “ the absence of essential elements of offence” and “the insignificant of act” was proposed to delete from Ch. 2, Art. 11 Criminal Code of Ukraine that phrase as “... has not caused significant damage ...”. According to tins, it is proposed to write Ch. 2, Art. 11 Ukraine in the following way: “An action or inaction is not a criminal offense that although fonnally contains the signs of the act provided by this Code, but in accordance with insignificance they do not contain the public danger which is necessary for the criminal infraction of public insecurity, so that they could not cause any significant damage”.
дис. ... к.ю.н. : 12.00.08
Маломуж С.І. Малозначність діяння в кримінальному праві України: дис. ... канд. юрид. наук: 12.00.08 / Маломуж Сергій Ігорович. - Одеса, 2017. - 254 с.
Keywords: малозначність діяння; правопорушення; злочин; проступок; склад злочину; звільнення від кримінальної відповідальності; обставини, що виключають злочинність діяння; малозначительность деяния; правонарушение; преступление; состав преступления; освобождение от уголовной ответственности; обстоятельства, исключающие преступность деяния; the insignificance of act; offense; infraction; essential elements of offence; remission from criminal amenability; the circumstances that excluding criminality